Application of cellulases from an alkalothermophilic thermomonospora sp in biopolishing of denims - Anish, Ramakrishnan; Rahman, Mohammad Safikur; Rao, Mala (Biotechnology and Bioengineering, 2007)
Use of cellulase for denim washing is a standard eco-friendly technique to achieve desirable appearance and softness for cotton fabrics and denims. But enzymatic washing of denim till date involved acid cellulase (Trichoderma reesei) and neutral cellulase (Humicola isolens) the use of which has a drawback of backstaining of the indigo dye on to the fabric. Though it has been suggested that pH is a major factor in controlling backstaining there are no reports on use of cellulase under alkaline conditions for denim washing. In this study for the first time an alkali stable endoglucanase from alkalothermophilic Thermomonospora sp. (T-EG) has been used for denim biofinishing under alkaline conditions. T-EG is effective in removing hairiness with negligible weight loss and imparting softness to the fabric. Higher abrasive reactivity with lower backstaining was a preferred property for denim biofinishing exhibited by T-EG. The activities were comparable to acid and neutral cellulases that are being regularly used. The enzyme was also effective under non-buffering conditions which is an added advantage for use in textile industry. A probable mechanism of enzymatic finishing of cotton fabric has been represented based on the unique properties of T-EG.
Keywords: alkaline conditions; biopolishing; Cellulase; denim; Thermomonospora sp

Approach towards biocatalytic valorisation of barley beta-glucan for bioethanol production using 1,3-1,4 beta-glucanase and thermotolerant yeast - Divate, Rupesh; Menon, Vishnu; Rao, Mala (International Biodeterioration & Biodegradation, 2013)
The exploitation of renewable resource containing polymers other than cellulose and hemicellulose are critically important for the feasibility of biofuel production. The potential of 1,3-1,4 glucan 4-gluconohydrolyase mediated saccharification of barley beta-glucan (BG) was investigated for ethanol production using thermotolerant Saccharomyces sp. A maximum hydrolysis of 71% was obtained in 24 h using in-house produced 1,3-1,4 beta-glucanase from an alkalothermophilic Thermomonospora sp. whereas the hydrolysis was 100% with Accellerase (TM) 1000. The synergistic effect of beta-glucosidase and 1,3-1,4 beta-glucanase was demonstrated by the exogenous addition of beta-glucosidase to Thermomonospora 1,3-1,4 beta-glucanase which resulted in complete hydrolysis of BG. The hydrolysates of BG obtained using Accellerase or a cocktail of Thermomonospora 1,3-1,4 beta-glucanase and beta-glucosidase when fermented with free cells of Saccharomyces at 40 degrees C produced an ethanol yield of 0.44 g g(-1) and 0.46 g g(-1) respectively and when fermented with immobilized cells produced a yield of 0.49 g g(-1). The Ca-alginate immobilized yeast cells were reused nine times at 40 degrees C with 100% fermentation efficiency. The economics of barley-to-fuel ethanol program will ameliorate if in addition to barley starch, beta-glucan is also utilized. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-1; 4 Glucan 4-gluconohydrolyase; Barley beta-glucan; Ethanol; Hydrolysis; Synergism; Thermotolerant yeast